PENGARUH AMBLESAN TANAH (LAND SUBSIDENCE) TERHADAP LINGKUNGAN PERMUKIMAN DI DATARAN ALUVIAL SEBAGIAN KOTA SEMARANG - , Ir. Soedarsono, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Semarang as a one of big cities in Indonesia has an area 373,4 km2 with the number of inhabitants is 1,481,460 (2008). Geographically, while the southern side consists of denudasional structural hilly and volcanic hilly, in the northern side is alluvial plain. As dwellers increase, a construction was made in order to fulfill the need of houses and industry. Since land has been rare, an embankment of marshland and a shore reclamation were done. These leaded land subsidence increased. The effects of the land subsidence were such as temporarily tidal flood on the residentsâ area just adjacent to sea, this condition caused the damaged of houses and the infrastructures and yielded several illnesses occurred. The aim of this research is to observe the change of subsidence category, the cange of flooding area, the damages of infrastructures, and the quality of health due to flooding. This research was conducted by using the method of survey and laboratory. For the evaluation of land subsidence, the laboratory analysis was conducted by overlaying several maps: the map of cearing capacity, the map of the thickness of alluvial, the map of soil embankment, and the map of ground water settlement. This overlaying obtained the new map of land subsidence, then this new map is overlaid again with the previous map of land subsidence ( year of 2000), and the final result was the map of evaluation of land subsidence. To discover the changes of the area of flooding, the overlaying of the map of flooding in year of 1996 and 2010 was conducted, and the result of this was the map of flooding area change. For the purpose of obtaining those final maps, ArcGIS version 9.2 with Inverse Distance Weighted (IDW) method was occupied. However, the survey method was a way to analyze the damages of resident infrastructures and the decrease of dwellersâ health quality. The simple random sampling using SPSS version 14 was done. The result of research demonstrated that: 1) there was an increase of land subsidence covering the area of 270 Ha in Puri Anjasmoro, from small subsidence (0.00 â 0.10 cm/th) to medium subsidence (0.10 â 0.20 cm/th) in last 9 years. 2) Land subsidence with the area of 496.50 Ha in Marina, Indoperkasa, and PRPP, from 0.10 â 0.20 cm/th to > 20 cm/th in last 9 years was occurred. 3) a rise of flooding in residential area covering 29,62 Ha in last 14 years. 4) there was the damage of houses and infrastructure in residential area that was flooded. 5) several diseases occurred such as ISPA, diarrhea, and blood fever within environment that often flooded. 6) there was the decline of residential infrastructure quality about 20% and inhabitant health about 10.9%. in summary, the research demonstrated the change of subsidence category, the increase of flooding area, the damages of infrastructure, and the decrease of health quality.